2018
DOI: 10.1038/s41598-018-20602-y
|View full text |Cite|
|
Sign up to set email alerts
|

Chitosan nanoparticles functionalized with β-cyclodextrin: a promising carrier for botanical pesticides

Abstract: Carvacrol and linalool are natural compounds extracted from plants and are known for their insecticidal and repellent activities, respectively. However, their low aqueous solubility, high photosensitivity, and high volatility restrict their application in the control of agricultural pests. The encapsulation of volatile compounds can be an effective way of overcoming such problems. Inclusion complexes between beta-cyclodextrin (β-CD) and carvacrol (CVC) or linalool (LNL) were investigated. Inclusion complexes w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(47 citation statements)
references
References 70 publications
3
43
1
Order By: Relevance
“…There were no endothermic peak for AMD in loaded NPs, which showed that AMD had been incorporated with β-CD [50] . Similar results were obtained in the literature [52] .…”
Section: Resultssupporting
confidence: 92%
“…There were no endothermic peak for AMD in loaded NPs, which showed that AMD had been incorporated with β-CD [50] . Similar results were obtained in the literature [52] .…”
Section: Resultssupporting
confidence: 92%
“…However, it can be used as a carrier for pesticides when synthesized in the form of nanoparticles, either alone or in combination with other polymers . This double function as nanocarrier and active substance itself, in addition to its origin from a waste by‐product from the fishing industry, turns chitosan into a promising material for nanoformulating natural compounds …”
Section: Nanomaterials In Agriculturementioning
confidence: 99%
“…They have a hydrophobic core and a hydrophilic shell, and they self‐assemble in aqueous solutions with other components to form nanoparticles and aggregates. In addition, cyclodextrins can be conjugated with other nanomaterials, enhancing their characteristics as nanocarriers . They have been successfully loaded with fungicides and tested for treatment of fungal plant diseases in the field, or have been combined with fungicidal natural compounds such as geraniol…”
Section: Nanomaterials In Agriculturementioning
confidence: 99%
See 2 more Smart Citations